Spectroscopy peculiarities of electric arc discharge plasma with iron vapours - Murmantsev, A.; Veklich, A.; Boretskij, V. (Вопросы атомной науки и техники, 2021)
This work is devoted to spectroscopy peculiarities of electric arc discharge plasma with iron vapours. The solution of the main issue of optical emission spectroscopy, namely, selection of iron spectral lines, to study the parameters of non-uniform and non-steady-state plasma source, was considered within this paper. Specifically, the Boltzmann plots technique was used for detailed analysing of application possibility of Fe I spectral lines as well as for determination of plasma temperature. The spatial profiles of selected spectral line emission intensities were used to measure the radial distributions of plasma temperature of free-burning arc discharge between consumable electrodes at 3.5 A.